Developing and sustaining high-quality care for children with cancer: the WHO Global Initiative for Childhood Cancer - Roberta Ortiz; Liliana Vásquez; Bishnu Giri; Sharon Kapambwe; Issimouha Dille; Lamia Mahmoud; Sukhbaatar Bolormaa; Nazokat Kasymova; Andre Ilbawi (Pan American Health Organization, 2023)
Cancer is a major public health concern, impacting nearly 20 million people each year, and it is responsible for 1 in 6 deaths worldwide. The burden of cancer is increasing rapidly, straining health systems that are unable to prevent and manage the disease. Childhood cancer constitutes a significant and relevant public health challenge; it was the ninth leading cause of childhood disease globally, according to findings by the Global Burden of Disease 2017 study. Almost 80% of all children diagnosed with cancer live in low- and middle-income countries where treatment is often unavailable or unaffordable. As a result, only about 15-45% of these children survive compared with more than 80% in high-income countries. This represents a great health inequity. Delivering on the mandate provided by World Health Assembly resolution 70.12, WHO together with St. Jude Children's Research Hospital and other global partners launched the Global Initiative for Childhood Cancer at the United Nations General Assembly during the third High-level Meeting on the prevention and control of noncommunicable diseases in September 2018. The Initiative aims to increase global survival for children with cancer to at least 60% by 2030, while reducing suffering for all children with cancer. Five years after launching the Initiative, more than 70 countries across the World Health Organization's 6 regions have advanced to different phases of action through implementation of the Initiative's CureAll framework for action. Many successful approaches to implementing the CureAll pillars and enablers have demonstrated that improving care for children with cancer in low- and middle-income countries is possible as long as there is strong political will, multisectoral commitments and strategic investment.